Implementation of Contextual Teaching and Learning for Basic Natural Sciences at Madrasah Ibtidaiyah, UNUGHA Cilacap - Anastya Nida Alhana; Sedya Sentosa; Wida Nurul Azizah (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
This research aims to spread the implementation of learning innovations in Basic Natural Science courses at Madrasah Ibtidaiyah (MI Basic Science) using the Contextual Teaching and Learning (CTL) method at Nahdlatul Ulama Al Ghazali University (UNUGHA) Cilacap. The research method used is a case study with a qualitative approach. The aim of this research is to assess the effectiveness of the CTL method in increasing students’ understanding of Basic Natural Sciences and the extent to which this learning innovation is implemented in the MI educational environment. Through observations, interviews, and documentation analysis, this research describes how CTL is implemented, student responses, and its impact on understanding MI Basic Science concepts. The research results show that the implementation of CTL at UNUGHA Cilacap succeeded in increasing student involvement and the relevance of the material to everyday contexts. Students show increased understanding of MI Basic Science concepts, and this method provides significant support for achieving learning objectives. In conclusion, CTL is effectively applied in educational contexts, providing a stimulative and interactive learning environment. The practical implications of this research are recommendations for continuing to apply the CTL method in the development of the MI Basic Science curriculum